Periodontal Management in Periodontally Healthy Orthodontic Patients with Fixed Appliances: An Umbrella Review of Self-Care Instructions and Evidence-Based Recommendations - Federica Di Spirito; Alessandra Amato; Maria Pia Di Palo; Davide Cannatà; Francesco Giordano; Francesco D'Ambrosio; Stefano Martina (MDPI AG, 2023)
The present umbrella review aimed to characterize periodontal self-care instructions, prescriptions, and motivational methods; evaluate the associated periodontal outcomes; and provide integrated, evidence-based recommendations for periodontal self-care in periodontally healthy orthodontic patients with fixed appliances. The presently applied study protocol was developed in advance, compliant with the PRISMA statement, and registered on PROSPERO (CRD42022367204). Systematic reviews published in English without date restrictions were electronically searched until 21 November 2022 across the PROSPERO Register and Cochrane Library, Web of Science (Core Collection), Scopus, and MED-LINE/PubMed databases. The study quality assessment was conducted through the AMSTAR 2 tool. Seventeen systematic reviews were included. Powered and manual toothbrushes showed no significant differences in biofilm accumulation, although some evidence revealed significant improvements in inflammatory, bleeding, and periodontal pocket depth values in the short term with powered toothbrushes. Chlorhexidine mouthwashes, but no gels, varnishes, or pastes, controlled better biofilm accumulation and gingival inflammation as adjuncts to toothbrushing, although only for a limited period. Organic products, such as aloe vera and chamomile, proved their antimicrobial properties, and herbal-based mouthwashes seemed comparable to CHX without its side effects. Motivational methods also showed beneficial effects on periodontal biofilm control and inflammation, while no evidence supported probiotics administration.